“THE ROLE OF THE TEACHER IN ESP CLASSES” (Konferensiyalar | Conferences, 2024)
This scientific article explores the pivotal role of teachers in English for Specific Purposes (ESP) classes. ESP focuses on teaching English tailored to specific fields, such as business, medicine, or engineering. The teacher's role in ESP goes beyond traditional language instruction, encompassing needs analysis, materials development, and specialized teaching strategies. This article delves into the various aspects of the teacher's role in ESP classes and highlights the importance of their expertise in facilitating effective language learning in specialized contexts.